Middle ear neuroendocrine tumour-case report of a rare tumour of the temporal bone - Bhat, Manali; Vijayendra, H.; Vijayendra, Vinay Kumar; Mahajan, Nilesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Several conditions are known to present as masses in the middle ear medial to an intact tympanic membrane. Reddish masses that blanch on seigelization are usually paragangliomas. Sometimes, a high rising jugular bulb or an aberrant carotid artery can also be seen. Whitish masses are usually congenital cholesteatomas, tympanosclerosis, cartilage grafts that have been surgically placed, and rarely middle ear adenomas (MEA). An elderly male presented with decreased hearing, which was revealed to be secondary to a pale mass in the middle ear, displacing the intact tympanic membrane laterally. He underwent biopsy followed by complete excision of the mass, with preservation of the intact ossicular chain. There no evidence of recurrence on follow-up. Histopathology revealed the mass to be a MEA, also known as middle ear neuroendocrine tumour (MeNET). Middle ear neuroendocrine tumours are rare tumours. We describe the clinical presentation and management of this tumour.